2008
DOI: 10.1007/s10874-008-9112-3
|View full text |Cite
|
Sign up to set email alerts
|

A 10-year study of background surface ozone concentrations on the island of Gozo in the Central Mediterranean

Abstract: A 10-year study of surface ozone mixing ratios in the Central Mediterranean was conducted based on continuous ozone measurements from 1997 to 2006 by a background regional Global Atmospheric Watch (GAW) station on the island of Gozo. The mean annual maximum mixing ratio is of the order of 66 ppbv in April-May with a broad secondary maximum of 64 ppbv in July-September. No long-term increase or decrease in the background level of surface ozone could be observed over the last 10 years. This is contrary to observ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 36 publications
1
4
0
Order By: Relevance
“…For the shorter period 1996e2011 no significant O 3 trends were detected at CMN, in fairly good agreement with observations at other high mountain stations in Europe (e.g. Gilge et al, 2010;Logan et al, 2012;Parrish et al, 2012) and in the Mediterranean Islands of Cyprus (Kleanthous et al, 2014) and Malta (Saliba et al, 2008). Ordo nez et al (2007) suggested a strong relationship between stratosphere-to-troposphere exchange and O 3 changes at Alpine stations during 1990s: however no evident correlations existed between O 3 at CMN and long-term SI frequency variability or O 3 SI over the period 1996e2011.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…For the shorter period 1996e2011 no significant O 3 trends were detected at CMN, in fairly good agreement with observations at other high mountain stations in Europe (e.g. Gilge et al, 2010;Logan et al, 2012;Parrish et al, 2012) and in the Mediterranean Islands of Cyprus (Kleanthous et al, 2014) and Malta (Saliba et al, 2008). Ordo nez et al (2007) suggested a strong relationship between stratosphere-to-troposphere exchange and O 3 changes at Alpine stations during 1990s: however no evident correlations existed between O 3 at CMN and long-term SI frequency variability or O 3 SI over the period 1996e2011.…”
Section: Discussionsupporting
confidence: 89%
“…Not significant long-term O 3 trends were also detected by Saliba et al (2008. O 3 trends have been also calculated on a seasonal basis (DecembereFebruary: DJF; MarcheMay: MAM; JuneeAugust: JJA; SeptembereNovember: SON).…”
Section: Season Si Days Other Daysmentioning
confidence: 99%
“…Until the year 2014, besides the GAW/WMO Mt. Cimone Global Station (located in Northern Italy), only one other regional GAW/WMO station (El Gozo, Malta, see Saliba et al, 2008) provided longterm information on O 3 variability in this region. Only recently (2014, July), continuous O 3 observations have been started at the regional GAW/WMO station "N. Sarao" at Lampedusa Island (central Mediterranean Sea).…”
Section: Research Articlementioning
confidence: 99%
“…One is the direct transport of O 3 from urban areas, and the other is the transport of its precursors like NOx, VOC, CO, CH 4 (NMHC) (Trainer et al 1987), followed by in-situ photochemical O 3 production. In recent years, considerable work has been carried out to explore the influence of surface O 3 on climate change in various parts of the world (Oltmans and Komhyr 1976;Low et al 1992;Mazzeo et al 2005;Filella and Peñuelas 2006;Pudasainee et al 2006;Helmig et al 2007;Geng et al 2008;Saliba et al 2008;Poupkou et al 2009;Sicard et al 2009;Teixeira et al 2009;Geddes et al 2009;Yin Shan et al 2010;Hosseinibalam et al 2010;Banan and Latif 2011;Notario et al 2011). O 3 concentration is influenced by meteorological parameters including wind speed, wind direction, temperature and relative humidity (Lyons and Cole 1976;Aneja and Das 1995) over a location.…”
Section: Introductionmentioning
confidence: 99%